Oboshor : senior citizen health care and hospitality centre, Sreemangal, Sylhet. - Hoque, Mohammad Tanveerul (BRAC University, 2015)
This project report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture, 2015.